"But He Doesn't Know the Territory" : the Story behind Meredith Willson's The Music Man - Willson, Meredith, 1902-1984 (University of Minnesota Press, 2020)
Chronicles the creation of Meredith Willson's The Music Man--reprinted now as the Broadway Edition. Composer Meredith Willson described The Music Man as "an Iowan's attempt to pay tribute to his home state." Now featuring a new foreword by noted singer and educator Michael Feinstein, this book presents Willson's reflections on the ups and downs, surprises and disappointments, and finally successes of making one of America's most popular musicals. Willson's whimsical, personable writing style brings readers back in time with him to the 1950s to experience firsthand the exciting trials and tribulations of creating a Broadway masterpiece. Fresh admiration of the musical--and the man behind the music--is sure to result